EXTRACTION OF POLYSACCHARIDES FROM SEEDS AND PEEL OF MELON AND THE DETERMINATION OF THEIR COMPOSITION BY PHYSICO-CHEMICAL METHODS (Scientific journal of the Fergana State University, 2023)
Contentfruit peel and melon seeds were extracted with water and studied the amount of polysaccharides. According to the results obtained, it was determined that water-soluble polysaccharides (WSP) is 7.5%, pectic substances(PS) - 2.5% and hemicellulose– 2.1%. When studying the composition of the seeds, it was found that the VRPS is 7%, the PV is 2% and hemicellulose 0.5%.